R-loops as a trigger for intra- and extrachromosomal DNA amplification in cancer - Kovalenko, Tatyana F.; Abdurazakov, Amal; Antipova, Nadezhda V.; Shakhparonov, Mikhail I.; Pavlyukov, Marat S. (Frontiers in Cell and Developmental Biology, 2025)
R-loops consist of double-stranded DNA-RNA hybrids and a complementary DNA strand that is displaced from the duplex. R-loops play important role in numerous normal physiological processes, including DNA methylation, chromatin remodeling, RNA editing, replication, DNA repair, immunoglobulin class switching, and chromosome segregation during cell division. However, excessive or untimely formation of R-loops can lead to replicative collapse and subsequent DNA damage, resulting in genomic instability. One type of genomic rearrangements that is strongly associated with cancer malignancy is the extrachromosomal amplification of genes on circular DNA molecules (ecDNA). These molecules are relieved of hereditary constraints and conventional segregation laws and can endow cancer cells with the ability to rapidly change their genome, thereby accelerating tumor evolution and the development of therapy resistance. Multiple lines of evidence indicate that upregulated transcription of a gene can increase its susceptibility to amplification. Although the mechanisms underlying these processes are not yet fully understood, R-loops may play an important role in initiating gene amplification. In this review, we highlight the role of R-loops in replicative collapse, double-strand breaks, and DNA damage repair. We also provide examples of gene amplifications that is known to be induced by R-loops. Finally, we discuss amplification mechanisms in which involvement of R-loops has not yet been demonstrated, but appears highly likely.